Os verbos de estado no português brasileiro - Kely Stefani de Oliveira (2020)
In this dissertation, we take as object of study the verbs of state (VENDLER, 1967) of Brazilian Portuguese (PB), such as ter ‘have’, existir ‘exist’, saber ‘know’, custar ‘cost’, significar ‘mean’, morar ‘live’, carecer ‘lack’, aparentar ‘look like’, etc. The states describe situations that are durable, but that do not develop, do not progress in time and do not exhibit a definite final result. In other words, such verbs are characterized by having the aspectual values of static, durability and atelicity (VENDLER, 1967). As we are part of the Lexical Syntax-Semantic Interface research line (LEVIN, 1993; PINKER, 2013 [1989]; LEVIN; RAPPAPORT HOVAV, 2005; CANÇADO; GODOY; AMARAL, 2017), we share the assumption that some significant semantic characteristics of verbal items influence their syntactic behavior. Therefore, we aim to verify what are the semantic properties of these verbs that have an impact on grammar. Therefore, we seek to group the state verbs of PB into verbal classes (LEVIN, 2010; CANÇADO; GONÇALVES, 2016; CANÇADO; AMARAL, 2016), according to their common semantic and syntactic properties. In addition, based on the predicate decomposition approach (DOWTY, 1979; PINKER, 2013 [1989]; RAPPAPORT HOVAV; LEVIN, 1998; CANÇADO; AMARAL, 2016), we also propose semantic representation structures for the studied verb classes. We base our research on the proposals of Carlson (1977), Bach (1986), Pinker (2013 [1989]), Moreira (2000), Maienborn (2003), Rothmayr (2009) and Cunha (2004, 2011), who propose that state verbs constitute at least two or more classes. Based on these proposals, in particular, Carlson's (1977) proposal, it is observed that what groups the BP state verbs into different classes is the fact that these predicates are individual-level predicates, which denote permanent or stable, or Stage-level predicates, which denote transient or temporary states. We verified that these verbs are divided into two classes: in the “class of verbs of inherent state”, which is subdivided into the subclass of “existential verbs” and in the subclass of “reciprocal verbs”, and in the “class of intermittent state verbs”, which is subdivided into the subclass of “locative verbs” and the subclass of “measure verbs”. We conclude, therefore, that the BP data we present corroborates our initial hypothesis, that the aspectual class of the BP state verbs can be fragmented into smaller verbal classes, due to their semantic and syntactic diversity.